Optimizing Cr(VI) Reduction in Plastic Chromium Plating Wastewater: Particle Size, Irradiation, Titanium Dose - Angelica Santis; Oscar Arbeláez; Luz Angelica Cardenas; Jaritza Castellanos; Pablo Velasquez (Emerging Science Journal, 2024)
The preservation of the aquatic environment and water systems has been a fundamental objective that has led great scientists and researchers to seek new alternatives or techniques that allow the decontamination of water sources. The plastic chromium plating industries have been identified as important sources of contamination since their residues are characterized by having considerable amounts of hexavalent chromium Cr (VI), which alters the stability of water resources and can affect effluents on the surface and the subsoil. Given this problem, the need to improve the usual methods and techniques for wastewater treatment with more effective solutions, such as photocatalysis, which presents significant advantages over the inefficiency of traditional methods, is recognized. However, given the limited availability of research in the country that addresses the removal of hexavalent chromium from the wastewater of these industries, this work focuses on optimizing the process by varying conditions of variables such as particle size, catalyst dose, and irradiation time. The optimization of the photocatalysis process was evaluated using the Box-Behnken experimental design. The results show that contaminant removal occurred when the particle size was 0.177 mm. This particle size showed the highest photocatalytic activity, with 100% removal at 45 minutes. These findings represent a significant step towards solving the problem of contamination in this business sector by this pollutant and contribute to preserving our water resources. Doi: 10.28991/ESJ-2024-08-01-02 Full Text: PDF